Incidence and mortality rates for colorectal cancer in Puerto Rico and among Hispanics, Non-Hispanic Whites, and Non-Hispanic Blacks in the United States, 1998–2002 - Soto-Salgado, Marievelisse (2009)
BACKGROUND: Colorectal cancer (CRC) is the second most commonly diagnosed cancer in Puerto Rico (PR). In the United States of America (US), incidence and mortality rates of CRC show great variation by sex and race/ethnicity. Age-standardized incidence and mortality rates of CRC in PR and compared them with those of Hispanics (USH), non- Hispanic Whites (NHW) and non-Hispanic Blacks (NHB) in the US for the period 1998- 2002 were assessed. Incidence and mortality trends and relative differences among racial/ethnic groups by sex and age were determined. METHODS: Age-standardized rates [ASR(World)] were based on cancer incidence and mortality data from the PR Central Cancer Registry and SEER using the direct method. Annual percent changes (APC) and relative risks (RR) were calculated using Poisson regression models. RESULTS: For the 1998–2002 period, the APC of CRC incidence and mortality increased for men in PR, contrary to descending trends observed for other racial/ethnic groups. Overall period rates showed that in both sexes, PR had similar incidence and mortality rates from CRC as USH, but lower than those of NHW and NHB. However, PR men and women aged 40–59 years had higher risk of incidence and mortality when compared to their USH counterparts. CONCLUSIONS: Areas of concern include the increasing trends of CRC in PR and the higher burden of the disease among young Puerto Ricans as compared to USH. Further research should be performed in order to guide the design and implementation of CRC prevention and education programs in PR.